Export Performance In Cambodia, Laos, Myanmar And Vietnam (CLMV) Countries : Panel Data Analysis - Thida, Oo; Jerome, Kueh; Daw, Tin Hla; Aung, San Lwin (International Academy of Business and Economics (IABE), 2019)
Cambodia, Laos, Myanmar and Vietnam (CLMV) countries endeavour to increase the country's foreign exchange earnings by export performance. This study aims to identify the macroeconomic determinants of export performance of CLMV countries from the period of 2000 to 2015. This study adopted panel unit roots test, panel co-integration test and Pooled-mean group (PMG) method for testing and estimating purpose. Empirical findings show that the determinants of export performance are inflation, gross domestic and foreign direct investment, where there are positively associated with export performance of CLMV countries while the interest rate and exchange rate cannot influence the export performance in long run.